Pyramids of Playing Cards - Cabanilla, Carlos (2009)
Financial pyramids, as a global phenomenon, respond to social phenomena more related to ignorance and the desire to get easy money than with a financial issue in itself, which does not prevent it from generating a serious economic problem for those who bet all their capital on them. This document reviews the cases that have occurred in different parts of the world to generate a global view of the problem and seek action policies and laws that prevent this type of fraudulent business from continuing to appear and prosper.